SWEET POTATO CULTURE – PROMISING TREND OF RUSSIAN VEGETABLE GROWING - V. B. Podlesny (Овощи России, 2015)
Results of research of possibility of introduction of a new for the Russian Federation tuberous crop culture, sweet potato, are presented. The influence of planting dates on the yield of this culture was studied. According to the field experiment, the high yield of sweet potato tuber and resistance to diseases and pests were revealed.